Internalization of Environmentally Conscious Character Based on Ecological Citizenship at Junior High School - Nur Azizatur Rahmawati; Iqbal Arpannudin; Tasya Juliani Jasmarnisa; Aprillianata Aprillianata; Idang Ramadhan; Choirunnisa Amalia; Dominico Khalik (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2026)
This study aims to analyze the process of internalizing an environmentally conscious character based on ecological citizenship at junior high school. The study uses a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation, and analyzed using an interactive analysis model. The results show that the internalization of environmental awareness values occurs gradually and continuously in accordance with Krathwohl's affective domain, including the stages of receiving, responding, valuing, organization, and characterization. This process is reinforced through the integration of the four main dimensions of ecological citizenship, namely environmental knowledge, environmental attitudes, environmental skills, and environmental participation. The findings reveal that teacher role modeling, environmentally-friendly school policies, contextual learning, environmental projects, and synergy between schools, parents, and the community are the main factors supporting the internalization of values. Meanwhile, differences in students' levels of awareness, consumerist culture, and inconsistent role modeling in the family environment are obstacles that need to be overcome. This research contributes to the development of civic education studies by emphasizing the role of the affective domain in shaping an environmentally conscious character as the civic identity of students oriented towards sustainability.